Russia: holy or bourgeois-democratic? The controversy over S. Graham`s works during the First World War - Tretyakova Svetlana Nikolayevna (Studia Humanitatis, 2018)
The article examines the Russian society’s perception of the image of Russia created by the British traveller and writer S. Graham during the First World War. He advocated originality of Russia and saw her power in conservative traditions and deep religiosity. Although in bourgeois-democratic circles his writings were heavily criticized because his perception of Russia was wrong and caused damage to Russian-British relationship. A famous writer Maxim Gorky also considered such image to be bad for Russia.